PENGARUH QUALITY ASSURANCE DAN ISO 9000 TERHADAP KINERJA PROGRAM STUDI (STUDI PADA SEBUAH PERGURUAN TINGGI SWASTA DI YOGYAKARTA) - Aftoni Sutanto (Optimum: Jurnal Ekonomi dan Pembangunan, 2013)
Higher education is very important for the community. The college is an institution that organizes the process of education or teaching, research and service to the community. This research was conducted at a private university in Yogyakarta. The purpose of this research was to examine the influence of Quality Assurance and ISO 9000 on performance. The population of this research is the entire department. The sampling technique using saturated or census sampling technique, i.e. by using all components of the population considered to be able to assess the implementation of the Quality Assurance (QA) and the implementation of ISO 9000. The respondents in this study is the Chairman or Secretary of department. Technique of data analysis in this study uses the program of Generalized Structured Component Analysis (GSCA) to perform analysis of hypothesis testing. The result show that the diversity of variable QA, ISO and performance can be explained by models research with having value as fit as much as 73,6 %. The remaining 26,4 % described by other variables.Variable QA influential not significantly to the performance of a course of study in college. Variable ISO 9000 influential not significantly to the performance of course of study. While variable QA influential positive and significantly to ISO 9000. On the contrary, variable ISO 9000 influential positive and significantly to QA.